Measurement of the perceptions of human resource practices in a seemingly collectivistic culture - Anton Grobler; Sonja Grobler; Rose Mathafena (SA Journal of Human Resource Management, 2019)
Orientation: Human resources (HR) practices and specifically the perceptions thereof are not only important for organisational strategy and performance but have a direct impact on employee attitudes and behaviour. The accurate measurement of these perceptions is therefore important.